Ethical Issues in Rural Counselling Practice - Schank, Janet A. (Canadian Journal of Counselling and Psychotherapy, 2009)
Counsellors in rural areas find themselves facing unique challenges in striving to practice ethically and meet the needs of clients and communities. These challenges include dealing with: (1) multiple relationships, (2) limits of competence and resources, (3) geographic or professional isolation, (4) community values and expectations, and (5) inter-agency relationships. These challenges lead rural counsellors to examine and question their daily practice and lives in an attempt to balance ethical codes with the realities of rural life. Further illumination of the issues, along with suggestions to minimize practice risk, can contribute to the ethical practice of counselling that is most appropriate to rural areas and small communities.